2015
DOI: 10.1016/j.drugalcdep.2014.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Post-exposure prophylaxis use and recurrent exposure to HIV among men who have sex with men who use crystal methamphetamine

Abstract: Background Men who have sex with men (MSM) who use crystal methamphetamine (CM) are at increased risk for HIV infection. Post-exposure prophylaxis (PEP) is a useful HIV prevention strategy if individuals are able to identify high-risk exposures and seek timely care, however to date there has been limited data on the use of PEP by CM users. Methods A retrospective cohort study of all PEP prescriptions (N=1,130 prescriptions among 788 MSM) at Fenway Community Health in Boston, MA was undertaken. Multivariable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Furthermore, while two US studies found significant associations between recreational drug use and nPEP awareness or use , our study and another in New York City did not find a significant association . Nevertheless, MSM who have sex under the influence of various substances are generally more vulnerable to HIV infection , so we must ensure that these subgroups are appropriately informed of the availability and utility of nPEP.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, while two US studies found significant associations between recreational drug use and nPEP awareness or use , our study and another in New York City did not find a significant association . Nevertheless, MSM who have sex under the influence of various substances are generally more vulnerable to HIV infection , so we must ensure that these subgroups are appropriately informed of the availability and utility of nPEP.…”
Section: Discussionmentioning
confidence: 99%
“…(20) It is likely that the use of PrEP by MSM who use other stimulants, such as crystal methamphetamine, may have similar effects. It has been well established that crystal methamphetamine and cocaine use are associated with higher-risk sexual behavior and incident HIV infection,(5,7,10,12,21) and previous studies have shown stronger associations between stimulant use and serodiscordant condomless anal intercourse than with alcohol use. (22) Stimulant users may therefore be particularly good candidates for PrEP, and understanding perceived barriers and facilitators to uptake and adherence may improve effectiveness of PrEP implementation programs.…”
Section: Discussionmentioning
confidence: 99%
“…(7,12) Since optimal adherence is required to achieve PrEP efficacy and subsequently decrease risk of HIV acquisition, substance use could limit the effectiveness of PrEP if substance using MSM are unable to take PrEP as prescribed. Although prior studies have suggested that stimulant use did not affect PrEP adherence(16), in the current study substance users expressed concern about their ability to adhere to treatment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations